2012
DOI: 10.1155/2012/891201
|View full text |Cite
|
Sign up to set email alerts
|

Is the Macronutrient Intake of Formula-Fed Infants Greater Than Breast-Fed Infants in Early Infancy?

Abstract: Faster weight gain early in infancy may contribute to a greater risk of later obesity in formula-fed compared to breast-fed infants. One potential explanation for the difference in weight gain is higher macronutrient intake in formula-fed infants during the first weeks of life. A systematic review was conducted using Medline to assess the macronutrient and energy content plus volume of intake in breast-fed and formula-fed infants in early infancy. All studies from healthy, term, singleton infants reporting val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 88 publications
6
86
0
7
Order By: Relevance
“…A recent systematic review summarised the results of ‘mature’ HM samples (taken 2–4 weeks postnatally) 7, a total of the following: 415 for protein, 476 for carbohydrate and 567 for lipids, pooling data from a minimum of 18 studies worldwide, with the largest sample size of 71 in any single study. Our study is therefore far larger than any other reported, allowing informative associations with HM macronutrient contents in the range of the previously pooled meta‐analysed values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review summarised the results of ‘mature’ HM samples (taken 2–4 weeks postnatally) 7, a total of the following: 415 for protein, 476 for carbohydrate and 567 for lipids, pooling data from a minimum of 18 studies worldwide, with the largest sample size of 71 in any single study. Our study is therefore far larger than any other reported, allowing informative associations with HM macronutrient contents in the range of the previously pooled meta‐analysed values.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the slower infancy weight gain in breast‐fed babies is a result of lower total calorie intake or related to the nutrient composition of human breast milk (HM). Previous studies documenting HM energy or macronutrient contents have been recently reviewed 7, 8. Most were performed in small sample sizes, and few attempted to assess the influence of HM composition on subsequent infancy growth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributable to low self-regulation of food intake and over-consumption of energy in formula-fed infants. 46,47 Adjusted for corresponding growth measure at 6 months; the other 3 dietary patterns; household income; maternal age, race/ethnicity, education level, pre-pregnancy BMI, gestational diabetes, gestational weight gain; and child gender and gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Three stages are differentiated: colostrum (1-5 days post-delivery), transitional milk (6-15 days post-delivery) and mature milk (>15 days post-delivery). The difference in the composition of main macronutrients between these stages is well documented (Jenness, 1979;Jensen, 1999;Hester et al, 2012;Guesnet et al, 2013;Michalski, 2013). Less data is available about the variation of composition and structure of lipids in mature milk as lactation time progress.…”
Section: Fields Of Innovations Corresponding To Staging Infant Formulmentioning
confidence: 94%